Enhancement of the stability and cytotoxicity of berberine by liposomal nanocarriers for gastric cancer treatment and its application in gummy candy - Abolhasanzadeh, Narges; Dehghan, Gholamreza; Abbaspour-Ravasjani, Soheil (Frontiers in Gastroenterology, 2024)
IntroductionBerberine (BER), an isoquinoline alkaloid derived from the plant Berberis Vulgaris, is traditionally used to treat different types of disorders, such as cancer. However, its therapeutic application is limited due to poor solubility and low bioavailability. So, the main objective of the present work was to synthesize BER-loaded liposomes to enhance the solubility of BER. BER-loaded liposomes were synthesized using the thin-film hydration method.MethodsThe prepared liposomes were characterized for size, surface charge, in vitro release, and cytotoxicity. Then, the synthesized nano-liposomes were used to enrich gummy candies, and physicochemical properties such as water activity (aw), instrumental texture, and sensory perception of the products were tested.Results and DiscussionThe cell viability assay was performed on MKN-45P gastric cancer cell lines, and the results revealed that BER-loaded liposome had better cytotoxicity on MKN-45P cells than free BER. The IC50 values were calculated to be 66.72 µg/mL and 52.58 µg/mL for free BER and BER-loaded liposomes, respectively. Flow cytometric analysis demonstrated a significant anticancer effect of BER-loaded liposomes compared to free BER. These findings indicate that encapsulating BER preserves its antioxidant activity and enhances its bioavailability.